Developing Wordwall Evaluations in Blended Islamic Education Using the Smith and Ragan Model - Zh, Miftah Hur Rahman; Putra, Muhammad Fatih Budiman; Kuswandi, Dedi; Wedi, Agus; Ardiansyah, Arief (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2024)
Islamic religious education plays a crucial role in shaping the character and morality of individuals in the context of formal education. In the growing digital era, the use of blended learning has become popular and raising the need to develop an appropriate learning evaluation. This research aims to develop an evaluation of Islamic learning in the context of blended learning with wordwall media using the Smith and Ragan model. a developmental research design method was used to analyse the learning context, student needs, and learning tasks, in addition the strategy and assessment phases are also crucial stages of this development process. Data were obtained through interviews, observation, questionnaires, and documentation. Research instruments included questionnaires, interview guides, and observation lists, which were then analysed using qualitative and descriptive quantitative approaches. Drawing from the analysis findings, a dynamic and participatory assessment approach was formulated, leveraging the wordwall platform. Additionally, strategies for structuring, executing, and overseeing evaluations were devised to guarantee their efficacy. The results show that the development of this evaluation has the potential to improve the quality of sslamic learning in the digital era by providing a more diverse, effective and engaging learning experience for students. This research makes a significant contribution to the literature on the use of technology in Islamic religious education in blended learning.